Labour Market Outcomes of Immigrants in Germany – The Importance of Heterogeneity and Attrition Bias - Michael Fertig; Stefanie Schurer (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
Heterogeneity in the ethnic composition of Germany's immigrant population renders general conclusions on the degree of economic integration difficult. Using a rich longitudinal dataset, this paper tests for differences in economic assimilation profiles of four groups of foreign-born immigrants and ethnic Germans. The importance of time-invariant individual unobserved heterogeneity and panel attrition in determining the speed of assimilation is analysed. We find evidence for heterogeneity in the assimilation profiles for both annual earnings and unemployment probabilities. Robust assimilation profiles are found for two cohorts only. Omitted variables, systematic sample attrition and the presence of second generation immigrants in the sample influence the speed of assimilation, but do not change the overall picture.
Keywords: I12; C23; 330; Unobserved heterogeneity; panel attrition; sample selection; fixed effects; migration; Migranten; Ethnische Gruppe; Soziale Integration; Berufliche Integration; Schätzung; Deutschland